Synthesis and analysis of various modulo adders - Shaheen Khan, Zainul Abdin Jaffery, Khwaja M. Rafi, Irshad, Nadeem Ahmad (International Journal of Advanced Science and Technology, 2020)
Modulo addition is the crucial part for designing a RNS system. This paper present study of some of the most widely used mod adders and their simulation and implementation using 28/32 nm Synopsys Armenia Education Department (SAED) library saed32hvt_ff0p85v25c. Various techniques of modulo addition are compared based on the basic performance parameters like area, delay and power.